2018
DOI: 10.1016/j.copbio.2017.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Engineering microbial communities using thermodynamic principles and electrical interfaces

Abstract: Microbial communities present the next research frontier. We argue here that understanding and engineering microbial communities requires a holistic view that considers not only species-species, but also species-environment interactions, and feedbacks between ecological and evolutionary dynamics (eco-evo feedbacks). Due this multi-level nature of interactions, we predict that approaches aimed soley at altering specific species populations in a community (through strain enrichment or inhibition), would only hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…These electron acceptors were chosen because of their overlapping electrochemical potential window in saltwater medium. This electrochemical window is also consistent with common redox pairs involved in intracellular metabolism . In addition, bidirectional bacterial electron transfer can be influenced by the concentration of nitrate, while Co(II) ions are a low‐redox potential heavy metal suitable for affecting the electrochemical processes in the cell.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…These electron acceptors were chosen because of their overlapping electrochemical potential window in saltwater medium. This electrochemical window is also consistent with common redox pairs involved in intracellular metabolism . In addition, bidirectional bacterial electron transfer can be influenced by the concentration of nitrate, while Co(II) ions are a low‐redox potential heavy metal suitable for affecting the electrochemical processes in the cell.…”
Section: Resultssupporting
confidence: 77%
“…In general, there was a nonlinear decrease in the luminescence generated from the cells as the electrochemical potential became more negative between 0.3 V to 0.23 V vs NHE. This was also the potential range of nicotinamide and flavin cofactors used in intracellular and extracellular processes . The luminescence from the cells exposed to Co(II) (0.4 ± 0.1 RLU/CFU) was approximately half the intensity of cells exposed to 0.05 mM nitrate (1.3 ± 0.3 RLU/CFU).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Species, as members of a community, typically influence each other's growth and metabolism in several modes [41]. Interactions can be classified in two groups: (i) Direct, through physical contacts, and (ii) Indirect, either through the excretion of signal molecules (inhibitors/stimulators) or changing environmental growth factors (like pH and gas composition) [42].…”
Section: Nature Of Interactionsmentioning
confidence: 99%
“…Considering this interconnected set of redox reactions can crucially allow us to consider electronic circuits as an analogy to metabolic systems [64] on one hand, and to attempt their manipulation by electrochemical means on the other 65 , 66 , 67 . Indeed, it has been shown that influencing the ratio of key electron shuttles (e.g.…”
Section: Pathway-centric Views Of Metabolism and Its Shortcomingsmentioning
confidence: 99%